Penerapan Algoritma Decision Tree C4.5 Untuk Klasifikasi Mahasiswa Berpotensi Drop out Di Universitas Advent Indonesia - Daniel Sinaga; Edwin J Solaiman; Fergie Joanda Kaunang (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2021)
One of the factors that determine the quality of higher education is the percentage of students' ability to complete their studies on time. At present, the problem of student failure and the factors causing it to be an interesting topic to research. Higher education institutions need to detect the behavior of students who have an